The Impact of Supply Chain Practices on Sme Companies in Melaka - Samsuddin, Nurshamimah; Nor, Maliza Mohd; Sulaiman, Masri; Yusof, Aini Qamariah Mohd; Osman, Shahariah (School of Social Sciences, USM, 2017)
The supply chain has become crucial day by day. This is due to supply chain practices are giving the impact for the organization performance. The purpose of study is to find out the impact of supply chain practices on organization performance focusing SME companies. Based on previous researcher, there are four variables namely postponement, information sharing, strategic supplier partnership and customer relationship has been used to measure the organizational performance. There are 200 questionnaires been send out to the respondent who are currently work in SME. Based on the data collected the results show significant relationship between the supply chain practices and SME companies performance through the tested variables. At the end of the study, researcher has put some recommendations to improve the quality of future research in this area.